2013
DOI: 10.1586/erd.12.65
|View full text |Cite
|
Sign up to set email alerts
|

Improving retrieval rates for retrievable inferior vena cava filters

Abstract: The introduction of retrievable inferior vena cava (IVC) filters was an important step in the evolution of deep vein thrombosis/pulmonary embolism management. Their removability makes them preferred to permanent filters in many cases. IVC filter retrieval often occurs at a suboptimal rate, leading to complications associated with long-term placement. Improving retrievability includes solutions for patients being lost to follow-up, filter malpositioning, need arising for permanent IVC filtration, filtration req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…However, few “retrievable filters” are actually removed, with most published series documenting a retrieval rate between 20% and 50% [40] with mean retrieval rate of 34% [46]. Suboptimal IVC filter retrieval rate can lead to complications associated with long-term placement [47]. Low retrieval rates are mainly due to loss of followup.…”
Section: Efficacy Safety and Retrievabilitymentioning
confidence: 99%
“…However, few “retrievable filters” are actually removed, with most published series documenting a retrieval rate between 20% and 50% [40] with mean retrieval rate of 34% [46]. Suboptimal IVC filter retrieval rate can lead to complications associated with long-term placement [47]. Low retrieval rates are mainly due to loss of followup.…”
Section: Efficacy Safety and Retrievabilitymentioning
confidence: 99%
“…However, reviews of actual clinical practice reveal retrieval rates as low as 22%. 10 A systematic review in 2011, which included 37 studies and 6,834 patients, suggests that the mean retrieval rate was 34% and that “most of the filters became permanent devices.” 11 …”
Section: Discussionmentioning
confidence: 99%
“…16 Another study found that filter tilt, malpositioning, and longer duration of filter placement are common causes of retrieval failure, but that retrievability is still preferable to placing permanent filters. 17 IVCF placement has been associated with an increased incidence of proximal DVT, and the risk seems to be greater as duration of indwelling increases. 4 This study has several limitations.…”
Section: Complications and Effectiveness Of Ivcfsmentioning
confidence: 98%